Co-creating Urban Commons Through Community-Engaged Pedagogies (EAAE Annual Conference Proceedings, 2023)
The importance of empowering and engaging citizens in the shaping of their living environments to ensure a sustainable and affordable development and promote a sense of community has been highlighted in recent years (UN-Habitat). Citizens and professionals (architects, public institutions, private enterprises) are called to adopt new roles within the spatial design and provision process, which often challenges the ability of the latter to respond effectively to the rising need for a communityengaged design approach.